Nitric oxide signal is required for glutathione-induced enhancement of photosynthesis in salt-stressed Solanum lycopersicum L - Cong, Yundan; Chen, Xianjun; Xing, Jiayi; Li, Xuezhen; Pang, Shengqun; Liu, Huiying (Frontiers in Plant Science, 2024)
Reduced glutathione (γ-glutamyl-cysteinyl-glycine, GSH), the primary non-protein sulfhydryl group in organisms, plays a pivotal role in the plant salt stress response. This study aimed to explore the impact of GSH on the photosynthetic apparatus, and carbon assimilation in tomato plants under salt stress, and then investigate the role of nitric oxide (NO) in this process. The investigation involved foliar application of 5 mM GSH, 0.1% (w/v) hemoglobin (Hb, a nitric oxide scavenger), and GSH+Hb on the endogenous NO levels, rapid chlorophyll fluorescence, enzyme activities, and gene expression related to the Calvin cycle in tomato seedlings (Solanum lycopersicum L. cv. 'Zhongshu No. 4') subjected short-term salt stress (100 mM NaCl) for 24, 48 and 72 hours. GSH treatment notably boosted nitrate reductase (NR) and NO synthase (NOS) activities, elevating endogenous NO signaling in salt-stressed tomato seedling leaves. It also mitigated chlorophyll fluorescence (OJIP) curve distortion and damage to the oxygen-evolving complex (OEC) induced by salt stress. Furthermore, GSH improved photosystem II (PSII) electron transfer efficiency, reduced QA -accumulation, and countered salt stress effects on photosystem I (PSI) redox properties, enhancing the light energy absorption index (PIabs). Additionally, GSH enhanced key enzyme activities in the Calvin cycle and upregulated their genes. Exogenous GSH optimized PSII energy utilization via endogenous NO, safeguarded the photosynthetic reaction center, improved photochemical and energy efficiency, and boosted carbon assimilation, ultimately enhancing net photosynthetic efficiency (Pn) in salt-stressed tomato seedling leaves. Conversely, Hb hindered Pn reduction and NO signaling under salt stress and weakened the positive effects of GSH on NO levels, photosynthetic apparatus, and carbon assimilation in tomato plants. Thus, the positive regulation of photosynthesis in tomato seedlings under salt stress by GSH requires the involvement of NO.